The Role of Nanofibrous Structure in Osteogenic Differentiation of Human Mesenchymal Stem Cells with Serial Passage - Nguyen, Luong Thi Hien (2016)
Using scaffolds with autologous stem cells is a golden strategy for the treatment of bone defects. In this strategy, human mesenchymal stem cells (hMSCs) have often been isolated and expanded in vitro on a plastic surface to obtain a sufficient cell number before seeding on a suitable scaffold. Materials & Methods: Investigating the influence of serial passages (from passage two to passage eight) on the abilities of proliferation and osteogenic differentiation of hMSCs on 24-well tissue culture polystyrene plates and poly L-lactic acid electrospun nanofibrous scaffolds was performed to determine how prolonged culture affected these cellular abilities and how the nanofibrous scaffolds supported the osteogenic differentiation potential of hMSCs. Results & Conclusion: Serial passage caused adverse changes in hMSCs characteristics, which were indicated by the decline in both proliferation and osteogenic differentiation abilities. Interestingly, the poly L-lactic acid nanofibrous scaffolds showed a significant support in recovering the osteogenic abilities of hMSCs, which had been severely affected by prolonged culture.